Evaluating the Watching-Based Learning Model for Elementary School Students: A Case Study in Muhammadiyah Bandongan - Wahyuningsih, Yuli; Abdul Majid, Ikhwanuddin; Efendi, Faisal; Purnanto, Arif Wiyat (Journal of Educational Management and Strategy, 2025)
The purpose of this study is to evaluate the implementation of the Watching-Based Learning Model as a multimodal learning approach in Grade IV at SD IT Muhammadiyah Bandongan. This research employed a qualitative design using naturalistic observation supported by interviews and field notes collected over one month. The findings indicate that the multimodal learning model has been implemented at a level of 40%. Within this framework, visual representation accounts for 80% and audiovisual representation for 20%. In terms of multimodal literacy, visual literacy contributes 60% while critical multimodal literacy constitutes 40%. The visual literacy phase is identified as the initial stage, where students demonstrate comprehension of simple and familiar multimodal texts with predictable structures. In contrast, the critical multimodal literacy phase is positioned at the exploratory stage, where students begin to integrate strategies to interpret the content, purpose, and form of multimodal texts. The model is supported by three dominant media: textbooks (61%), PowerPoint (31%), and wall crafts (8%). This study highlights the relevance of multimodal learning in enhancing elementary students’ literacy development by integrating diverse media and literacy phases. The implications suggest that a balanced incorporation of visual and critical multimodal literacy can strengthen students’ comprehension and interpretation skills, offering valuable insights for curriculum development and classroom practice in primary education.